Analysis of Thermo chemical behaviour of Calotropis procera parts for their Potentiality. Issue 1 (31st December 2022) - Radhaboy, G.; Pugazhvadivu, M.; Ganeshan, P.; Ramshankar, P.
Abstract : Calotropis procera ( C.procera) is a xerophytic perennial shrub or small tree of flowering species belongs to the family Asclepiadaceae (Giant milkweed). It is native to tropical and subtropical Africa, South West Asia (India, Pakistan, Afghanistan, Iran, Arabia and Jordan) and common in the Middle East and its weed that grows profusely without management on road sides and waste lands. In this work, the stem, leaf, flower and the whole plant of C.procera were characterised to evaluate the suitability for use as renewable energy feedstock. The ultimate and proximate analyses were carried out to determine the elemental composition and volatile matter, ash and fixed carbon content respectively. Thermogravimetric analyses (TGA) were performed to study the pyrolysis and combustion characteristics. The chemical groups present in the plant parts were measured by FTIR spectroscopy analysis. The proximate and ultimate compositions of plant parts were similar to other lignocellulosic biomass. The whole plant exhibited a heating value of 21.85 MJ/kg whilst the mean higher heating value of the plant parts was 17.947 MJ/kg. The TGA profiles under nitrogen atmosphere presented significant mass loss of the plant parts. The pyrolysis of flower showed the highest reactivity with mass loss of 74%. The combustion profiles presented two distinct degradation stages each with a sharp peak indicating the oxidation of hemicellulose, cellulose, lignin and char. The average ignition and burnout temperatures estimated from the TG and DTG curves of plant parts was 240.25°C and 493.25°C respectively. The thermal behaviours under nitrogen and oxygen environment indicated that the plant parts are suitable for both pyrolysis and combustion processes. The FTIR analysis indicated the presence of aldehydes, ketones, organic acids, phenols and alcohols.